A novel continuous capnodynamic method for cardiac output assessment in a porcine model of lung lavage. Issue 8 (4th June 2015) - Hällsjö Sander, C.; Hallbäck, M.; Suarez Sipmann, F.; Wallin, M.; Oldner, A.; Björne, H.
<x xml:space="preserve">Abstract</x> Background We have evaluated a new method for continuous monitoring of effective pulmonary blood flow (COEPBF), i.e. cardiac output (CO) minus intra‐pulmonary shunt, during mechanical ventilation. The method has shown good trending ability during severe hemodynamic challenges in a porcine model with intact lungs. In this study, we further evaluate the COEPBF method in a model of lung lavage. Methods COEPBF was compared to a reference method for CO during hemodynamic and PEEP alterations, 5 and 12 cmH2O, before and after repeated lung lavages in 10 anaesthetised pigs. Bland–Altman, four‐quadrant and polar plot methodologies were used to determine agreement and trending ability. Results After lung lavage at PEEP 5 cmH2O, the ratio of arterial oxygen partial pressure related to inspired fraction of oxygen significantly decreased. The mean difference (limits of agreement) between methods changed from 0.2 (−1.1 to 1.5) to −0.9 (−3.6 to 1.9) l/min and percentage error increased from 34% to 70%. Trending ability remained good according to the four‐quadrant plot (concordance rate 94%), whereas mean angular bias increased from 4° to −16° when using the polar plot methodology. Conclusion Both agreement and precision of COEPBF were impaired in relation to CO when the shunt fraction was increased after lavage at PEEP 5 cmH2O. However, trending ability remained good as assessed by the four‐quadrant plot, whereas the mean polar angle, calculated by the polar plot, was wide.